Unveiling Attitudes Towards Open Access Monographs in the European Research Area - Manista, Gabriela; Maryl, Maciej; Wnuk, Magdalena (Septentrio Conference Series, 2024)
Academic books remain crucial in scholarly production, particularly within the SSH. However, open-access policies have predominantly focused on journal articles, leaving monographs less regulated. The adoption of OA practices across universities, research institutions, and publishers has spurred efforts to evaluate their impact on research dissemination and visibility (Bryan & Ozcan, 2021; Robinson-Garcia et al., 2020; Vincent-Lamarre et al., 2016). Studies have examined how OA mandates influence publication rates (Azadbakht et al., 2023) and what incentives increase researchers' OA participation (Hadad et al., 2023; Koley & Lala, 2022; Terán & Dávila, 2023). Despite the focus on journals, OA books are gaining traction, presenting challenges for policy regulation and impact assessment (Laakso, 2022). The PALOMERA (Policy Alignment of Open Access Monographs in the European Research Area; Grant agreement ID: 1010942701), a Horizon Europe project, aims to address the challenges behind implementing books in OA policies by analysing the policy landscape and then developing a harmonised set of recommendations for various stakeholders. This paper analyses 42 interviews conducted with key stakeholders – researchers, librarians, publishers, research funding agencies, and policymakers across the ERA to understand their attitudes towards OA monographs and identify common trends. Based on analyses of the qualitative material, we can distinguish three major factors contributing to the attitudes toward open access monographs: Policy gaps and publishing challenges. The absence of clear regulations for OA monographs does not inhibit their publication but introduces challenges in copyright, licensing, and technological infrastructure. While national OA policies are scarce, funder and institutional requirements often compensate, though they lack comprehensive reward systems to incentivise OA publishing. Multilingualism and visibility. While promoting transparency, open science may inadvertently disadvantage non-English publications. Interviews suggest that OA monographs in local languages, like Bulgarian, face lower visibility compared to English-language works, highlighting a potential imbalance in internationalisation strategies and petrify the domination of English-language commercial publishers. Prestige. OA books are still frequently viewed as less prestigious than traditional printed books. This perception is influenced by concerns that OA formats are still associated with vanity publishing and predatory practices. This stigma may stem from the fact that OA monographs are less common than journal articles and that it takes time for OA to build equivalent academic prestige. The dataset and analysis contribute to the ongoing struggle to base open science discourse on solid and empirical findings to advocate for comprehensive policies for scholarly content. The conclusion will address incorporating this work into building successful OS strategies for social sciences and humanities in the framework of SCIROS (Strategic Collaboration for Interdisciplinary Research on Open Science in the SSH) project.